Development of Packaging Design of Rendang Powder Seasoning at UD Serba Guna Abadi with Value Analysis - Faradisyi, Zahra; Mulyati, Guntarti Tatik; Nugrahini, Arita Dewi (Department of Agroindustrial Technology, Faculty of Agricultural Technology UGM, 2024)
According to the National Socio-Economic Survey (SUSENAS) in 2020, the average consumption of packaged seasoning from 2016 to 2020 grew the highest compared to other types of food at 9.13%. One of the most popular packaged seasonings is rendang powder, often accompanied by problems such as easily torn primary packaging, poor packaging, and incomplete packaging label information. To overcome these problems, developing a packaging design and determining the shelf-life is necessary. This research aims to create a concept for packaging powdered rendang seasoning that offers the highest value and to determine the product's shelf-life using the chosen packaging. The packaging design for powdered rendang seasoning was developed using value analysis and shelf-life was determined using the Arrhenius model through Accelerated Shelf-Life Testing (ASLT). Based on the research, out of five packaging concepts tested, it was found that packaging concept 2 has the highest value of 1.31 with packaging specifications using a packaging material of aluminum foil combined with plastic. A stand-up bag with a rectangular clear section, the package has a notch, zipper, and full labeling. Packaging concept 2 is the chosen packaging concept that meets the research objectives. It addresses the issue of easily torn packaging and includes improvements in packaging quality and more comprehensive packaging labeling. Based on the shelf-life determination of 3 packaging that has the highest values and 1 control package, packaging concept 2 has the longest shelf-life of 131 days, and based on the results of the proximate test conducted, packaging concept 2 is packaging with a sample that does not differ significantly (p value>0.05) with the control sample for all parameters quality.